2008
DOI: 10.1111/j.1462-2920.2008.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community response to a release of neat ethanol onto residual hydrocarbons in a pilot‐scale aquifer tank

Abstract: The microbial community response to a neat ethanol release (E100, 76 l) onto residual hydrocarbons in sandy soil was evaluated in a continuous-flow 8 m(3) pilot-scale aquifer tank, simulating a release at a bulk fuel terminal. Microbial genotypic shifts were assessed using quantitative real-time PCR analysis. High ethanol concentrations in the capillary fringe at potentially toxic levels, exceeding 100,000 mg l(-1), were tolerated by the microbial community. The high biochemical oxygen demand exerted by ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 50 publications
1
24
2
Order By: Relevance
“…Therefore the presence of ethanol and ethanol-derived acetate in groundwater can contribute to longer BTEX plumes (Ruiz-Aguilar et al, 2002;Corseuil et al, 2011) increasing the risk of human exposure ). These observations have been corroborated by laboratory studies (Corseuil et al, 1998;Da Silva and Alvarez, 2002;Cápiro et al, 2007Cápiro et al, , 2008, field research (Ruiz-Aguilar et al, 2002;Corseuil et al, 2011) and modeling studies (Heermann and Powers, 1998;Mcnab et al, 1999;Molson et al, 2002;Gomez et al, 2008;Alvarez, 2009, 2010). Nevertheless, the intensity of these effects can be system specific, which underscores the need for simple models that facilitate preliminary risk assessment and evaluate the potential performance of natural attenuation.…”
Section: Introductionsupporting
confidence: 64%
“…Therefore the presence of ethanol and ethanol-derived acetate in groundwater can contribute to longer BTEX plumes (Ruiz-Aguilar et al, 2002;Corseuil et al, 2011) increasing the risk of human exposure ). These observations have been corroborated by laboratory studies (Corseuil et al, 1998;Da Silva and Alvarez, 2002;Cápiro et al, 2007Cápiro et al, , 2008, field research (Ruiz-Aguilar et al, 2002;Corseuil et al, 2011) and modeling studies (Heermann and Powers, 1998;Mcnab et al, 1999;Molson et al, 2002;Gomez et al, 2008;Alvarez, 2009, 2010). Nevertheless, the intensity of these effects can be system specific, which underscores the need for simple models that facilitate preliminary risk assessment and evaluate the potential performance of natural attenuation.…”
Section: Introductionsupporting
confidence: 64%
“…Following collection of the final round of aqueous samples from the sideports at the termination of the experiment (day 525, PV 116.2; Table 1), solid phase samples were obtained from a 1 cm radius around each sideport by destructive sampling. To enumerate dechlorinating bacteria by qPCR, DNA was extracted from solid and aqueous samples following established protocols (described in the Supplemental material) (Amos et al, 2009;Cápiro et al, 2008Cápiro et al, , 2014.…”
Section: Aquifer Cell Operation and Sample Collectionmentioning
confidence: 99%
“…For example, acetate concentrations above 64 mg/L (Corseuil et al 2011a) and 75 mg/L (Ramos et al 2013) were found to be responsible for the inhibition of anaerobic biodegradation of benzene. Also, ethanol has been shown to decrease the relative abundance of benzene, toluene, and xylene degrading bacteria (Cápiro et al 2008).…”
Section: Effects Of the Presence Of Biodiesel In The Anaerobic Degradmentioning
confidence: 99%